Social reality in communication in rural areas - Peñarrieta-Muñoz, Yandry Javier; Moreira-Morales, Sabina Eroina; Candela-Muñoz, Ulfrido Siffrido; Alcívar-Moreira, Mirla Katherine; Zambrano-Villegas, Yenny Alexandra (International research journal of management, IT and social sciences, 2023)
Social reality is the construction that arises from the interaction of individuals in a specific context, many students from rural areas operate in environments that can affect their integral development, a situation where emphasis is placed on promoting communication as a support element. The objective of the study is to determine the relationship between social reality and communication in rural areas. The methodology is mixed, integrated by qualitative and quantitative methods. The technique used was the student survey and documentary analysis. The study population was made up of 105 high school students from the Dr. Carlos Romo Educational Unit. The results reflect that in the rural area there are risk factors that can affect the learning and integrity of the students. It is concluded in the importance of communication between school and family to face these situations.